Fiqh siyasah; tinjauan tentang pemikiran politik hukum tata negara dalam perspektif islam - Syahputra, Yusuf - (Maliki Interdisciplinary Journal, 2025)
Fiqh Siyasah or political law in Islam, is a branch of fiqh that discusses the principles and rules in regulating government and relations between the state and society from an Islamic perspective. As an integral part of Islamic teachings, fiqh siyasah regulates all aspects of political life by referring to the main sources of Islamic law, namely the Al-Qur’an, hadith, ijma’ (ulama consensus), and qiyas (analogy). This article aims to provide an in-depth review of siyasah fiqh, by highlighting the basic principles that lead to justice, deliberation (syura), trust, people’s welfare (maslahah), and leadership based on good values in the Islamic state system. Apart from that, this article also discusses how the application of siyasa fiqh was applied in Islamic history, starting from the Caliphate era to the development of modern countries. The challenges of siyasa fiqh in the context of modern countries, especially in countries that adopt a secular government system, are also an important discussion. In Indonesia, siyasah fiqh remains relevant in providing guidance for the formation of policies based on Islamic principles, even though it must adapt to the reality of religious pluralism and the ideology of Pancasila. In the end, siyasah fiqh offers guidelines for a government that is fair, transparent, and pro-people’s welfare, and able to adapt to the political dynamics of the modern era.